The effect of institutional quality on innovativeness of firm in emerging economies - Osei, Kwaku (Univerzita Pardubice, 2024)
The aim of the study was to assess the institutional quality and infrastructural base of the state on the innovativeness of firms in emerging economies. The study considered key institutional arrangement and their propensity to affect the innovativeness of firms leading to economic growth. The specific research objectives were to examine the impact of foreign direct investment net outflows on institutional quality and the innovativeness and economic growth of Emerging economies, to evaluate effect of government effectiveness on the institutional quality and the innovativeness and economic growth of Emerging economies, and to assess the influence of rule of law on the institutional quality and innovativeness of economic growth of Emerging economies. The study found that the impact of foreign direct investment outflows on firm innovativeness is mixed. In some countries, such as Romania and Poland, foreign direct investment outflows have a positive impact on firm innovativeness. However, in other countries, such as the Czech Republic and Greece, foreign direct investment outflows have a negative impact on firm innovativeness. The study also found that the impact of government effectiveness on firm innovativeness is mixed. In Hungary and the Czech Republic, there is a statistically significant negative relationship between government effectiveness and firm innovativeness. The study found that Rule of law has a strong positive impact on firm innovativeness. The study found that countries with stronger rule of law tend to have more innovative firms. The study found that this was because stronger rule of law provides a more stable and predictable environment for businesses, which allows them to take risks and invest in innovation.
Vliv institucionální kvality na inovativnost firmy v rozvíjejících se ekonomikách
Keywords: innovativeness; firms; emerging; economies; Hungary; Czech Republic; rule of law; inovace; firmy; rozvíjející se ekonomiky; Maďarsko; Česká republika; právní stát